The identification methods of coal seam fracture based on seismic attributes - Li Dong; Shi Suzhen (矿业科学学报, 2017)
For the safety and effective exploitation of coal-bed gas, the coal seam fracture is predicted comprehensively based on the seismic attributes.Firstly, the attributes of the variance, the curvature, the dip and the ant were discussed, which were suitable for identifying the fracture.Meanwhile, combining with the actual 3D seismic data of LE block, the attribute slice was extracted from the targeted coal seam.According individual attribute, the seam fracture was predicted preliminarily.Secondly, the above attributes were mixed by artificial neural network method.The prediction results of the seam fracture were obtained.Finally, through the comprehensive analysis of single attribute and multiple attribute prediction results, the development region of the target coal were delineated in the study area.Compared with the imaging logging and the geological data, attribute prediction results were consistent with the actual results.Therefore, the identification method based on seismic attributes can provide reliable geological basis for the exploration and development of coalbed methane.